A poster presentation as an evaluation method to facilitate reflective thinking skills in nursing education - M.M. Chabeli (AOSIS, 2002)
This article seeks to establish whether the poster presentation of a specific theme can facilitate the student's thinking skills in nursing education. A qualitative, exploratory, descriptive and contextual research design where twenty students volunteered to take part in the study by signing an informed consent was followed. Descriptive naïve sketches were used for data collection followed by individual interviews to validate the findings. Data was analysed by means of the descriptive method of open coding of Tesch (in Creswell, 1994:155). DENOSA's ethical standards for research (1998:7) were considered.